Prevalence of Intestinal and Urinary Parasitic and Bacterial Pathogens Among Staffs of Four Residential Halls of a Public University in Bangladesh (Bioresearch Communications, 2026)
Background: Intestinal parasitic infections and antimicrobial resistance (AMR) are major public health concerns in developing countries, particularly among individuals living or working in densely populated institutional settings. This study aimed to assess the prevalence of intestinal parasites and antibiotic resistance patterns among residential hall staffs at a public university in Bangladesh in order to identify the risk factors for transmission of pathogens to residential students. Methods: A total of 100 stool samples were collected from 4 residential hall staffs of a public university and analyzed microscopically for protozoan and helminth infections. Additionally, 10 stool and 13 urine samples from hall staffs, along with 14 revived clinical urinary isolates, were tested for antimicrobial susceptibility using the Kirby-Bauer disc diffusion method. Univariate and multiple quasi-Poisson regression analyses were conducted to examine the association between parasite count and various demographic and behavioral risk factors. Results: The overall prevalence of parasitic infections was 100%, with all participants harboring at least one intestinal parasite. Protozoan infections were present in 100% of individuals, while helminths were found in 94%, with Blastocystis sp. and Ascaris lumbricoides being the most prevalent. The Quasi-Poisson regression analyses revealed that none of the variables were statistically significantly associated with higher parasite counts. Stool isolates showed the highest resistance (60%) to moxifloxacin. Clinical UTI isolates showed alarmingly high resistance (≥85.7%) to all tested fluoroquinolones, with nalidixic acid resistance reaching 92.8%. Complete sensitivity (100%) to ofloxacin (OFX) was observed in E. coli isolates from healthy individuals' urine samples, highlighting a stark contrast with the 85.7% resistance seen in clinical isolates. Conclusion: The study reveals a critical parasitic disease burden and rising antimicrobial resistance among university staffs, emphasizing the urgent need for integrated public health interventions. These should include hygiene education, deworming programs, routine microbial surveillance, and strict antibiotic stewardship to reduce transmission among students and preserve treatment efficacy.Bioresearch Commu. 12(1): 1981-1990, 2026 (January)